Neuromuscular factors predicting lower limb explosive strength in male college sprinters - Li, Y.; Guo, Q.; Shao, J.; Gan, Y.; Zhao, Y.; Zhou, Y. (Frontiers in Physiology, 2025)
Purpose: This study aimed to explore the effects of neural and muscular factors on lower limb explosive strength in male college sprinters, and build models based on those factors to identify the key neuromuscular factors that predict the rate of force development (RFD) and 30 m sprint time.